Akselerasi Digitalisasi Umkm Sebagai Stimulus Pertumbuhan Produk Domestik Bruto (PDB) - Zalfa Afrillia; Elsa Setiawati; Windi Lastria Meilani; Syafaatul Hidayati (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the role of MSME digitalization acceleration as a stimulus for Gross Domestic Product (GDP) growth in Indonesia through a qualitative literature review approach. MSMEs have an important contribution to the national economy because they absorb labor, increase household income, and strengthen domestic economic stability. However, the rapid development of digital technology has encouraged MSMEs to adapt through digital transformation to improve competitiveness and productivity. This research uses qualitative methods by literature review from scientific journals, government reports, and macroeconomic publications related to MSME digitalization and economic growth in Indonesia. The results indicate that MSME digitalization contributes significantly to increasing productivity, expanding market access, strengthening financial inclusion, and increasing business efficiency. In addition, digital transformation among MSMEs supports national economic growth through increased production, consumption, investment, and employment opportunities. The study concludes that strengthening digital infrastructure, improving digital literacy, and expanding access to financing are important strategies to accelerate MSME digitalization and encourage sustainable GDP growth in Indonesia.